PENGARUH IMPLEMENTASI MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT DALAM MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Silvia Suryanti (Journal of Pedagogy and Online Learning, 2024)
The purpose of this study was to improve the learning outcomes of students in Islamic Religious Education subjects in class V of SDN 11 Taratak Surian by using the Teams Games Tournament (TGT) learning model. The method used in this research is descriptive method. The form of this research is class action research. The subjects in this study were all fifth grade students of SDN 11 Taratak Surian, totaling 20 students consisting of 12 male students and 8 female students. The results of the study were as many as 9 students (45%) reached learning completeness with a new class average of 64, then after reflection in cycle II, the final results of cycle II showed an increase in student learning outcomes which can be seen from the increasing average value, namely at the end of cycle II as many as 18 students who were complete (scored >70). So that learning completeness reaches 90% of the total number of students and the class average value reaches 86 so that it can be said to be effective.